ANALISIS PELAKSANAAN STRATEGI PROMOSI PRODUK MOBIL HYUNDAI ( Kasus Pada Pt. Hyundai Mobil Indonesia Cabang Pekanbaru) - Feber Slamat; Meizy Heriyanto (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2015)
Sales promotion is efforts conducted by company in order to advising, informing about their product and company is good in the form of service and also product of finished goods middle of social life, consumer or client, so that the product become recognized and used by cutomer with all the form of amenity and advantage facility of given promotion.This research conducted at PT Hyundai, at Tuanku Tambusai street Pekanbaru. The purpose of this Research is to analyse execution of promotion from PT. Hyundai Pekanbaru. In this research is methodologies used by descriptive, where sample used by that is buyers of Hyundai Cars Pekanbaru and as source of information is party HRD, Front of Office and Manager marketing, to determine sampel use formula Slovin, method of sampling by accidental sampling, data collecting is through interview, observation and quesioner. From result analyse promotion execution conducted by Hyundai Pekanbaru covering advertisement activity Advertising, Personal Selling, Publicity and Sales Promotion, expressing that the promotion activity be at good enough category with percentage note apart between goodness adversely very small.Keywords: promotion